2002
DOI: 10.1103/physrevc.66.061302
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of random interactions

Abstract: It is argued that spectral features of quantal systems with random interactions can be given a geometric interpretation. This conjecture is investigated in the context of two simple models: a system of randomly interacting d bosons and one of randomly interacting fermions in a j=7/2 shell. In both examples the probability for a given state to become the ground state is shown to be related to a geometric property of a polygon or polyhedron which is entirely determined by particle number, shell size, and symmetr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The Casimir operators appearing in Eq. (11) are known in closed form, (12) in terms of the operatorsT…”
mentioning
confidence: 99%
“…The Casimir operators appearing in Eq. (11) are known in closed form, (12) in terms of the operatorsT…”
mentioning
confidence: 99%
“…Chau et al showed that all energies are confined to a convex polytope (i.e., a convex polyhedron in d dimensions) and that only the states located at the vertices of this polyhedron can become the ground state [19]. The probability for a state at vertex j to become the ground state depends on the angle f j θ jf , where the sum is over all faces that contain the vertex j , and θ jf is the angle subtended at vertex j in the face f .…”
Section: Covariancesmentioning
confidence: 99%
“…[19], spectroscopic properties of quantum systems with random interactions were given a geometric interpretation. In particular, it was shown that diagonal Hamiltonians, i.e., those whose energy eigenvalues depend linearly on the two-body matrix elements, can be associated with a geometric shape (convex polyhedron) defined in terms of coefficients of fractional parentage and/or generalized coupling coefficients.…”
Section: Covariancesmentioning
confidence: 99%
See 2 more Smart Citations